Pengaruh Kualitas Pelayanan terhadap Kepuasan Masyarakat dalam Penyelesaian Perselisihan Ketenagakerjaan di Disnakertrans Sumut - Stefana, Maria; Lubis, Khairunnisah (Universitas Medan Area, 2025)
The resolution of labor disputes is a crucial aspect in maintaining the stability of industrial relations in Indonesia. The Manpower and Transmigration Office plays an important role in providing quality labor conflict resolution services, which affects the level of community satisfaction. This study aims to analyze the influence of service quality on community satisfaction in resolving labor disputes in North Sumatra Province. A quantitative approach was used with a survey method on 234 randomly selected respondents. Data analysis was carried out using descriptive and inferential statistical techniques, including regression tests to identify relationships between research variables. The results showed that service quality had a significant effect on community satisfaction, with an R Square value of 42.9%. Therefore, improving the quality of services, such as transparency and responsiveness, needs to be a priority to increase public trust in the government in resolving labor disputes.